Design and development of orchard autonomous navigation spray system - Wang, Shubo; Song, Jianli; Qi, Peng; Yuan, Changjian; Wu, Hecheng; Zhang, Lanting; Liu, Weihong; Liu, Yajia; He, Xiongkui (Frontiers in Plant Science, 2022)
Driven by the demand for efficient plant protection in orchards, the autonomous navigation system for orchards is hereby designed and developed in this paper. According to the three modules of unmanned system "perception-decision-control", the environment perception and map construction strategy based on 3D lidar is constructed for the complex environment in orchards. At the same time, millimeter-wave radar is further selected for multi-source information fusion for the perception of obstacles. The extraction of orchard navigation lines is achieved by formulating a 4-step extraction strategy according to the obtained lidar data. Finally, aiming at the control problem of plant protection machine, the ADRC control strategy is adopted to enhance the noise immunity of the system. Different working conditions are designed in the experimental section for testing the obstacle avoidance performance and navigation accuracy of the autonomous navigation sprayer. The experimental results show that the unmanned vehicle could quickly identify the obstacle, and make an emergency stop and around action when setting a stationary person or a thin column of different materials as an obstacle; The unmanned vehicle could also identify the obstacle quickly and an emergency stop and find a rather narrow feasible area when a moving person or a different thin column is used as an obstacle. In the navigation accuracy experiment, the average navigation error in both experiments was within 15 cm, meeting the requirements for orchard spray operation. A set of spray test experiments were designed in the final experimental part to further verify the feasibility of the system developed by the Institute.